Application of Smart Mobile Devices in Electronic Design Education: Multidimensional Interaction Model and Learning Outcomes Assessment - Huang, Liang; Luo, Haifeng (International Journal of Interactive Mobile Technologies (iJIM), 2024)
With the rapid advancement of technology, smart mobile devices are increasingly being integrated into the educational domain, showing significant potential, particularly in electronic design education. Traditional classroom teaching methods face limitations in information delivery and student interaction, while the introduction of smart mobile devices brings new opportunities to classroom instruction. Through smart mobile devices, educators can organize teaching activities more flexibly, and students can engage in classroom interactions in various forms, greatly enhancing teaching effectiveness and learning experiences. Although numerous studies have explored the application of smart mobile devices in education, most focus on single-dimensional interaction models, overlooking the potential of multidimensional interactions. Additionally, traditional methods for assessing learning outcomes often rely on qualitative analysis and post-class tests, which fail to comprehensively and in realtime reflect students’ learning states and emotional changes. This paper aims to construct a multidimensional interaction model for electronic design education classrooms based on smart mobile devices and to assess learning outcomes through real-time analysis of students’ emotions and feedback data, thereby optimizing teaching strategies. This study not only provides new perspectives and methods for the application of smart mobile devices in education but also offers practical guidance for teaching reforms and innovations in electronic design education, holding significant theoretical and practical value.